2012
DOI: 10.1007/s10928-012-9254-4
|View full text |Cite
|
Sign up to set email alerts
|

General relationship between transit compartments and lifespan models

Abstract: Transit compartment models (TCM) are important tools in pharmacokinetic/pharmacodynamic (PKPD) modeling. In this work we investigate the relationship between TCMs with arbitrary initial values and lifespan models (LSM) with non-constant past and constant lifespan. We show that the total population in all transit compartments converges to a LSM, if the number of compartments n tends to infinity. The key to obtain this result is to establish a relationship between the initial values of the TCM and the non-consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The parameters T RBC , M CFU and M NOR were fixed to 120, 4 and 4 days, respectively RSE relative standard error DDE add-on extensions benefit from increasing their TOL/ ATOL by 1-2 unit (U) to obtain the desired precision in numerical integration of DDEs. The estimate of the lifespan of the apoptotic cells T D was 3.39 days which was consistent with previous publications [1,20]. The results in Table 5 also showed that the parameters were estimated with a very good precision (RSE% \ 30%).…”
Section: Lifespan Based Tumor Growth Inhibition Modelsupporting
confidence: 89%
See 1 more Smart Citation
“…The parameters T RBC , M CFU and M NOR were fixed to 120, 4 and 4 days, respectively RSE relative standard error DDE add-on extensions benefit from increasing their TOL/ ATOL by 1-2 unit (U) to obtain the desired precision in numerical integration of DDEs. The estimate of the lifespan of the apoptotic cells T D was 3.39 days which was consistent with previous publications [1,20]. The results in Table 5 also showed that the parameters were estimated with a very good precision (RSE% \ 30%).…”
Section: Lifespan Based Tumor Growth Inhibition Modelsupporting
confidence: 89%
“…Data from both the control and drug treatment groups were used. The lifespan based TGI model has been introduced previously [1,20]. It assumes that the tumor is separated into two populations of cells: a proliferating population P(t) and an apoptotic population A(t).…”
Section: Lifespan Based Tumor Growth Inhibition Modelmentioning
confidence: 99%
“…Many PKPD models use transit compartments to incorporate delays [9] [11] , [39] . We used the lifespan model to describe the process of cell division, and since transit compartments are approximations of lifespan models, and are equivalent under certain conditions [40] , [41] , it was natural for us to describe the dying tumor cells using a lifespan model as well.…”
Section: Discussionmentioning
confidence: 99%
“…forcing input (Beq), so that . The exact solution may be written using the matrix exponential [ 9 , 27 ], or by using Laplace Transforms (Appendix 1.4 ). For the transit compartments, we find that where .…”
Section: Analytical Solutions For Equi-dosing Regimensmentioning
confidence: 99%
“…Transit compartment models have been proposed to capture delay effects in PK time courses, through a semi-mechanistic approach of increasing the number of compartments through which the drug is transferred en route to the central compartaament (blood) [ 26 , 27 , 32 , 33 , 44 , 46 , 47 ]. The development of “full” or accurate mechanistic physiologically-based PK models requires much experimental data and knowledge which may be unavailable.…”
Section: Introductionmentioning
confidence: 99%